Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob) - de Mazancourt, Valentin; Marquet, Gerard; Rogers, D. Christopher; Keith, Philippe (Zootaxa, 2018)
During field trips to Guam and Babeldaob Islands in Micronesia, freshwater shrimps were sampled and assigned either to Caridina brachydactyla De Man, 1908 or C. mertoni J. Roux, 1911 (Decapoda: Atyidae), following previous inventories. In combining morphological data with a genetical analysis, it appeared that all the specimens belonged to a new species, Caridina variabilis sp. nov., here described with its distribution. The status of this new species is clarified and finally, neither C. brachydactyla, nor C. mertoni occur in these two islands. DNA sequences of 16S were obtained from the syntypes of C. mertoni.